Eksistensi Tradisi Mupunjung Situs Lengkong Ciilat Desa Sukadana Kecamatan Sukadana Kabupaten Ciamis - Ahmad Rizky Fauzi (IAIN Syekh Nurjati Cirebon, 2023)
The existence of the Mupunjung tradition which still exists today is an interesting study material for writers. Mupunjung comes from the word munjung or ngunjung. Mupunjung has many meanings such as